2018
DOI: 10.1002/pits.22125
|View full text |Cite
|
Sign up to set email alerts
|

Can social support buffer the association between depression and suicidal ideation in adolescent boys and girls?

Abstract: The purpose of the current study is to investigate social support (from parents, classmates, teachers, and close friends) as a protective factor in the association between depression and suicidal ideation.Data on students' levels of social support, depression, and suicidal ideation were collected from 399 9th-grade students using the Child and Adolescent Social Support Scale (CASSS), the Children's Depression Inventory, 2nd Edition Short Version (CDI 2), and the Suicidal Ideation Questionnaire -Junior Version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 41 publications
6
42
1
Order By: Relevance
“…Its characterization resulted from the separation of avoidance and numbing symptoms (American Psychiatric Association, ). Individuals suffering from NACM have persistent negative beliefs and expectations about the self and the world and generate more negative emotions, all of which may promote antisocial behavior (Fredrick, Demaray, Malecki, & Dorio, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its characterization resulted from the separation of avoidance and numbing symptoms (American Psychiatric Association, ). Individuals suffering from NACM have persistent negative beliefs and expectations about the self and the world and generate more negative emotions, all of which may promote antisocial behavior (Fredrick, Demaray, Malecki, & Dorio, ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of avoidance symptoms on antisocial behavior was not significant among those with strong social support. One possible reason is that social support offers sufficient security and a sense of belonging (Fredrick et al, ). In this case, the avoidance of trauma cues may have temporarily enabled those participants to avoid the psychological impact imposed by their trauma, and thus their individual negative psychosomatic reactions were alleviated.…”
Section: Discussionmentioning
confidence: 99%
“…In a crosssectional sample of American adolescent college students, higher levels of perceived social support had a protective effect against suicidal behaviors through the promotion of self-efficacy (Thompson, Eggert, & Herting, 2000). Satisfactory perceived social support from parents and close friends has also been reported to have a buffering effect regarding the association between depression and suicidal ideation among male and female adolescents (Fredrick, Demaray, Malecki, & Dorio, 2018). Also, a number of researchers of the adolescent population have reported significant positive relationships between social support and self-esteem (Marshall, Parker, Ciarrochi, & Heaven, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide empirical bases for intervention and treatment of depressive symptoms, this study integrates these three variables and attempts to explore the potential psychological mechanisms behind them. In addition, because previous research suggested that both grade and sex may significantly affect parental attachment (Chen et al, ), expressive suppression (Dong & Zhang, ), and depressive symptoms (Cui, Shi, Zhang, & Yu, ; Fredrick, Demaray, Malecki, & Dorio, ; Luo, Xiang, Zhang, & Wang, ), we included these two variables as covariates in our data analyses. Therefore, based on the above literature review, we examined the relationships between parental attachment, emotion regulation (expressive suppression and cognitive reappraisal), and depressive symptoms among Chinese adolescents.…”
mentioning
confidence: 99%